Regional Environmental Non-Governmental Organizations: Between Resistance and Utopia, Some Reflections. (Revista Brasileira Multidisciplinar, 2008)
This paper has as its main objective the comprehension and analysis of the environmental action effectiveness of Non-Governmental Organizations (NGOs) which are inserted in the region of the Hydrographic Basins of rivers "Turvo" and "Grande", and their relation with the others who act in this interactive field in order to understand what is being built in these regions considering the environmental issue. Material and Methodology: direct research in the selected NGOs and bibliographic review: NGOs, environmental legislation and participative democracy. Results: Participation in the survey data for the diagnosis of the current situation of hydric resource and the establishment of guidelines for the Plan of Hydrographic Basins of "Turvo" and "Grande" – Report Zero and in the Basins of "Turvo" and "Grande" Committee, actions in Environmental Education and reforestation/revegetation of part of the riparian forest and the protection of water sources. Conclusion: The environmental NGOs have played the protagonist role in the process of social transformation, with representativeness and competence to add people, institutions and resources to defend environment. Their acts show evidences that it's possible to overcome the environmental damages and they contribute to a reflection about the environment, means of organization and popular participation. The NGOs actions are often blocked by the game of interests that feeds the backstage of environmental matter. Business people pressure, lack of political will from the politicians to break the favor culture that was taken forward in relation to big interests; all these factors take part in the inhibition circuit that hinders the NGOs acts many times.
Keywords: NGOs; Environment; Participative Democracy.